2016
DOI: 10.1016/j.pscychresns.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal striatal resting-state functional connectivity in adolescents with obsessive–compulsive disorder

Abstract: Neuroimaging research has implicated abnormalities in cortico-striatal-thalamic-cortical (CSTC) circuitry in pediatric obsessive-compulsive disorder (OCD). In this study, resting-state functional magnetic resonance imaging (R-fMRI) was used to investigate functional connectivity in the CSTC in adolescents with OCD. Imaging was obtained with the Human Connectome Project (HCP) scanner using newly developed pulse sequences which allow for higher spatial and temporal resolution. Fifteen adolescents with OCD and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…Even outside of active task engagement, nodes of the SN are abnormally hyperactive: increased resting state functional activity of the ACC, MDN (Rauch et al, 2006a; Bourne et al, 2012), dlPFC (Figee et al, 2014) and caudate nucleus (Graybiel and Rauch, 2000) has been noted in individuals with OCD. Frontostriatal functional connectivity stemming from the dlPFC (Vaghi et al, 2016), and altered striatal connectivity to the insula (Bernstein et al, 2016) has been linked to OCD severity.…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…Even outside of active task engagement, nodes of the SN are abnormally hyperactive: increased resting state functional activity of the ACC, MDN (Rauch et al, 2006a; Bourne et al, 2012), dlPFC (Figee et al, 2014) and caudate nucleus (Graybiel and Rauch, 2000) has been noted in individuals with OCD. Frontostriatal functional connectivity stemming from the dlPFC (Vaghi et al, 2016), and altered striatal connectivity to the insula (Bernstein et al, 2016) has been linked to OCD severity.…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…Our biomarker was unaffected by medication status, and the functional networks contributing to the biomarker were distributed widely, including the Although previous rs-fMRI studies revealed neurobiological abnormalities in patients with OCD, the generalizability of these findings is still elusive. In fact, even for the most promising fronto-striatal circuit hypothesis, the findings have been inconsistent 15,16,[24][25][26] ; that is, the fronto-striatal circuit in OCD was hypoconnected in some studies 25,26 and hyperconnected in others 15,16,24 . Although these inconsistencies might be due to the clinical characteristics of each dataset 25,26 , other studies suggested that the fronto-striatal circuit is not the only target should be considered.…”
mentioning
confidence: 99%
“…In fact, even for the most promising fronto-striatal circuit hypothesis, the findings have been inconsistent 15,16,[24][25][26] ; that is, the fronto-striatal circuit in OCD was hypoconnected in some studies 25,26 and hyperconnected in others 15,16,24 . Although these inconsistencies might be due to the clinical characteristics of each dataset 25,26 , other studies suggested that the fronto-striatal circuit is not the only target should be considered. In other words, studies have suggested that there were abnormalities in addition to those observed in the fronto-striatal circuit, including the frontoparietal and default mode networks 5,27,28 .…”
mentioning
confidence: 99%
“…In patients with OCD, abnormalities of cortico-striatal circuits that involve the orbitofrontal cortex, anterior cingulate cortex, prefrontal cortices, temporo-parieto-occipital areas, thalamus, and the striatum have been suggested, 81,82 as well as impaired striatal connectivity. 83 In patients with ADHD, dysfunctions in the cortico-striatal-thalamo-cortical circuits, 84 changes in cortical thickness and gyrification, 85 changes in the serotonin transporter binding potential, 86 changes in callosal thickness, 87 and reduced gray matter volumes in various regions of the brain are seen. 88,89 In addition, the severity of ADHD and OCD symptoms probably has neuroanatomical correlates.…”
mentioning
confidence: 99%